A review of bacterial cellulose-based drug delivery systems: their biochemistry, current approaches and future prospects. (17th March 2014) - Abeer, Muhammad Mustafa; Mohd Amin, Mohd Cairul Iqbal; Martin, Claire
Abstract: Objectives: The field of pharmaceutical technology is expanding rapidly because of the increasing number of drug delivery options. Successful drug delivery is influenced by multiple factors, one of which is the appropriate identification of materials for research and engineering of new drug delivery systems. Bacterial cellulose (BC) is one such biopolymer that fulfils the criteria for consideration as a drug delivery material. Key findings: BC showed versatility in terms of its potential for in-situ modulation, chemical modification after synthesis and application in the biomedical field, thus expanding the current, more limited view of BC and facilitating the investigation of its potential for application in drug delivery. Summary: Cellulose, which is widely available in nature, has numerous applications. One of the applications is that of BC in the pharmaceutical and biomedical fields, where it has been primarily applied for transdermal formulations to improve clinical outcomes. This review takes a multidisciplinary approach to consideration of the feasibility and potential benefits of BC in the development of other drug delivery systems for various routes of administration.